POLA ASUH ORANG TUA DALAM MENGEMBANGKAN PERILAKU KEAGAMAAN ANAK USIA 5-6 TAHUN DI DESA KOTO TUO PULAU TENGAH - S, Aidil; Adawiyah, Fatniaton (Yayasan Darussalam Bengkulu, 2022)
This study aims to determine the parenting style of parents in the village of Koto Tuo Pulau Tengah, to find out how the parenting style of parents in developing the religious behavior of children aged 5-6 in the village of Koto Tuo Pulau Tengah, to find out the inhibiting factors for parents in developing religious behavior for children aged 5-6. 5-6 years in the village of Koto Tuo, Pulau Tengah. In this study the researchers used a qualitative descriptive method, data collection was carried out in natural settings, primary data sources and data collection techniques were mostly on observation, in-depth interviews and documentation. In general, there are four kinds of data collection techniques, namely: observation, interviews, documentation and combination/tringulation to further refine this research. This study found that parenting by parents is different, ranging from authoritarian, democratic, and permassive parenting, but in using it has not been going well and not optimal. In developing religious behavior in children aged 5-6 years, parents play a role, starting from the attitude of the parents themselves to set an example for their children, and leaving the place of study so that children can learn more about religion, and in the family environment parents spend more time with children, starting from telling stories, inviting children to pray, inviting children to help their parents at home and getting children to do things according to religious orders such as praying, reading the Koran, reading prayers. and respect for their parents, as for the inhibiting factors in developing religious behavior, ranging from the low level of parental education so that parents have limited knowledge in developing children's behavior, the lack of consistency of parents in making decisions, and parents' negligence in controlling children when playing and playing. lack of awareness of parents in developing religious behavior in children. In the results of this study it was found that, parents have not been able to use the right pattern or method in educating children so that the pattern they apply is not optimal, in developing religious behavior parents must play an important role, starting from being a role model or example for children, and must being able to control their children in playing, the inhibiting factor is that parents have to ask a lot of questions and conduct discussions, either through religious leaders or through media that are very easy to reach at this time, such as internet media.